ESTIMATING THE PERFORMANCE OF THE GAKKUMDU IN HANDLING REPORTS AND FINDINGS OF VIOLATIONS OF THE 2024 ELECTIONS - Nurhayati, Dwi Astuti Wahyu (Universitas Riau Kepulauan, 2024)
: It is imperative that vulnerabilities in the 2024 election law enforcement system be identified in order to provide learning and development for election organisers and other law enforcement organisations. This study aims to comprehend the kinds of cases that remain unresolved, the actions that are taken, the opinions of GAKKUMDU, about the receipt of reports and violations, the challenges encountered in managing and resolving issues, and the perspectives that the public will have going forward regarding election dispute resolution. Using a juridical-normative approach, the research uses normative legal research methodologies to analyse the relevant legal norms in the context of addressing election-related criminal offences in 2024.The results show two different types of reports: one was registered and included the village heads' lack of neutrality, while the other four were not (distribution of staple food packages, damage to campaign media (APK and APS), lack of transparency by the Election Supervisory Body, and circulation of the